Shattering and yield expression of sesame (Sesamum indicum L) genotypes influenced by paclobutrazol concentration under rainfed conditions of Pothwar - Jahangir Ahmed; Ghulam Qadir; Muhammad Ansar; Fahad Masoud Wattoo; Talha Javed; Baber Ali; Romina Alina Marc; Mehdi Rahimi (BMC Plant Biology, 2023)
Abstract Seed shattering is a critical challenge that significantly reduces sesame production by 50%. These shattering losses can be reduced by selecting shattering resistant genotypes or by incorporating modern agronomic management such as paclobutrazol, which can boost productivity and prevent seed shattering in sesame. Two-years of field trials were conducted to examine the effect of sesame genotypes, environment, and paclobutrazol (PBZ) concentrations. Twelve sesame genotypes were used in a four-way factorial RCBD with three replications and five PBZ concentrations (T0 = Control; T1 = 150; T2 = 300; T3 = 450; and T4 = 600 mg L− 1) under rainfed conditions of Pothwar. The findings revealed significant variations in the major effects of all examined variables (genotypes, locations, years, and PBZ levels). Sesame genotypes PI-154304 and PI-175907 had the highest plant height, number of capsule plant− 1, seed capsule− 1, 1000 seed weight, biological yield, and seed yield, while also having the lowest seed losses and shattering percentage. Regarding environments, NARC-Islamabad generated the highest plant height, number of capsule plant− 1, shattering percentage, and biological yield; however, the URF-Koont produced the highest seed yield with the lowest shattering percentage. Additionally, plant height, capsules plant− 1, and biological yield were higher in 2021, while seed capsule− 1, 1000 seed weight, seed losses, shattering percentage, and seed yield were higher in 2020. PBZ concentration affected all measured parameters; plant height and number of seed capsule− 1 decreased with increasing PBZ concentrations. 450 mg L− 1 PBZ concentration generated the highest biomass, number of capsules plant− 1, and seed yield. At the same time, PBZ concentration 600 mg L− 1 generated the smallest plant, the lowest seed capsules− 1, the greatest thousand seed weight, and the lowest shattering percentage. The study concluded that paclobutrazol could dramatically reduce shattering percentage and shattering losses while increasing economic returns through better productivity. Based on the findings, the genotypes PI-154304 and PI-175907 with paclobutrazol level 450 mgL− 1 may be suggested for cultivation in Pothwar farming community under rainfed conditions, as they showed promising shattering resistance as well as enhanced growth and yield.